Demographic Change and Ethnic Survival among the Sedentary Populations on the Jesuit Mission Frontiers of Spanish South America, 1609–1803: The Formation and Persistence of Mission Communities in a Comparative Context - Jackson, Robert H (European Expansion and Indigenous Response, 2015)
Despite the effects of epidemics of highly contagious old world crowd diseases, the native populations living on the Paraguay and Chiquitos missions survived and retained a unique ethnic identity. A comparative approach shows how demographic patterns on the Paraguay and Chiquitos missions differed from other Spanish frontier missions.